Analisis Ekspresi Cyclin D1 dan COX-2 pada Berbagai Grading Histopatologik Karsinoma Endometrioid Ovarium - Erwin Sunardi; Endang Joewarini (Perhimpunan Dokter Spesialis Patologi Indonesia (IAPI), 2020)
BackgroundOvarian endometrioid carcinoma accounts for 10-15% of ovarian carcinomas, representing the second most common form ofovarian epithelial malignancy. Epithelial cell lines stably transfected to overexpress COX-2 exhibit a higher proliferation rate and aninhibition of apoptosis by prolongation of the G1 phase of the cell cycle through effects on Cyclin D1. The aim of this study is toanalyzed the correlation and differences between Cyclin D1 and COX-2 expressions in various histopathology grading ovarianendometrioid carcinoma.MethodsAn analitycal obsevational design with cross-sectional approach on sample from 23 paraffin blocks in Anatomical PathologyLaboratory Dr. Soetomo General Hospital. Microscopic slide stained with Cyclin D1 and COX-2 antibody. The imunohistochemistryexpression are evaluated and analyzed using Kruskal Wallis and Spearman test.ResultsThere were no differences Cyclin D1 expression in each grade, there were no differences COX-2 expression in each grade, therewas no correlation between Cyclin D1 and COX-2 expression all histopathologic grading, but have correlation expression in grade 3ovarian endometrioid carcinoma.ConclusionThis study showed that Cyclin D1 and COX-2 expression have no significant differences in various histopathological grading ovarianendometrioid carcinoma, and no correlation between Cyclin D1 and COX-2 expression all grade ovarian endometrioid carcinoma